A generic conceptual framework for a Total Information Networking System in construction. (1st January 2002) - Cheng, E.W.L.; Li, H.; Love, P.E.D.; Irani, Z.
The introduction and use of business-to-business electronic commerce is increasingly being used by the construction industry to expand their inter-organisational relationships within the supply chain. As a result, electronic commerce is being seen as an enabler for delivering significant strategic, tactical and operational benefits. In addition, it can be used as a system for sharing of construction information. Communication, coordination and inspection of the needs of different parties can be enhanced if different forms of information are effectively managed to complete the array of heterogeneous activities and tasks in a construction project. This paper proposes a Total Information Networking System (TINS) as a mechanism for conducting electronic commerce in construction. This system entails the development of a generic conceptual framework for structuring different kinds of information that flow within a company and its supply chain. The framework is based on three concepts. First, information can be classified according to the levels of goals and objectives to be achieved in a construction project. Second, information is either managerial or technical and thirdly, that information can be classified according to the phases of a construction project. Specifically, the framework represents the TINS to carve different forms of construction information into 30 manageable blocks. In doing so, establishing that Information Technology (IT) can be applied to the TINS and the associated Information Management Sub-Systems (IMSS).